Replication Data for: Consumer demand heterogeneity and valuation of value added pulse products: a case of precooked beans in Uganda - Aseete, Paul; Mutua, Mercy M.; Katungi, Enid M.; Bonabana-Wabbi, Jackline; Birachi, Eliud Abucheli; Ugen, Michael Adrogu (2018)
The data is from a survey conducted in Central Uganda in August 2015 by the National Crops Resources Research Institute in collaboration with CIAT-PABRA. This study investigated consumer demand heterogeneity and valuation of a processed bean product— “precooked beans” with substantially reduced cooking time. The study aimed at segmenting potential consumers of precooked beans and to determine their willingness to pay for the same when introduced on the market. Data file consists of variables on: i) consumer choices/preferences collected using a choice experiment, ii) social and demographics, iii) bean consumption dynamics, bean preparation methods, perceptions of food processing and market access.